2012
DOI: 10.1186/preaccept-1109880912645841
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 tumor suppressor network: focusing on its tail

Abstract: Germline mutations of the BRCA1 tumor suppressor gene are a major cause of familial breast and ovarian cancer. BRCA1 plays critical roles in the DNA damage response that regulates activities of multiple repair and checkpoint pathways for maintaining genome stability. The BRCT domains of BRCA1 constitute a phospho-peptide binding domain recognizing a phospho-SPxF motif (S, serine; P, proline; × varies; F, phenylalanine). The BRCT domains are frequently targeted by clinically important mutations and most of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 98 publications
(186 reference statements)
1
20
0
Order By: Relevance
“…Through its C-terminal BRCT domains, BRCA1 forms at least three different complexes, the BRCA1-A, BRCA1-B, and BRCA1-C complexes, by binding to Abraxas (Abra1), Bach1, and CtIP, respectively (5,7,8). Although all three complexes have been indicated in the role of BRCA1 in cell cycle checkpoint control and DNA repair, the BRCA1-A complex is known to target BRCA1 to DNA damage sites in response to DNA damageinduced Ub modification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Through its C-terminal BRCT domains, BRCA1 forms at least three different complexes, the BRCA1-A, BRCA1-B, and BRCA1-C complexes, by binding to Abraxas (Abra1), Bach1, and CtIP, respectively (5,7,8). Although all three complexes have been indicated in the role of BRCA1 in cell cycle checkpoint control and DNA repair, the BRCA1-A complex is known to target BRCA1 to DNA damage sites in response to DNA damageinduced Ub modification.…”
mentioning
confidence: 99%
“…Although all three complexes have been indicated in the role of BRCA1 in cell cycle checkpoint control and DNA repair, the BRCA1-A complex is known to target BRCA1 to DNA damage sites in response to DNA damageinduced Ub modification. The BRCA1-A complex contains at least five different components: Abraxas, NBA1/MERIT40, BRE, Rap80, and BRCC36 (8). Rap80 contains two ubiquitininteracting motif (UIM) domains that display a binding specificity toward Ub Lys-63 linkage chains generated through RNF8/RNF168 E3 ligases at sites of damage.…”
mentioning
confidence: 99%
“…Our current understanding of BRCA1's function is based largely on the role of its interacting proteins. 3,4 The RING domain has been shown to interact with 6 A number of substrates have been shown to be ubiquitinated by the BRCA1-BARD1 heterodimer. 7 For example, it was recently reported that BRCA1 monoubiquitinates histone H2A at satellite repeats and suppresses the expression of major and minor satellite transcripts.…”
Section: Functional Domains and Interacting Partners Of Brca1mentioning
confidence: 99%
“…BRCA1-B is composed of BRCA1, TopBP1, and BACH1, and is involved in DNA replication stress-induced checkpoint and DNA interstrand crosslink (ICL) repair [36]. BACH1 interacts with BRCT domain of BRCA1 through phosphoserine (p-S990) and its phosphorylation occurs in a cell-cycle-dependent manner, with the strongest interaction between BRCA1 and BACH1 during S-phase [14,37].…”
Section: Diverse Brca1 Complexesmentioning
confidence: 99%